Kinerja Lembaga Pengelola Hutan Desa Muara Danau Kabupaten Muara Enim, Provinsi Sumatera Selatan - Fito Apriandana; Rahmat Safe'i; Indra Gumay Febryano; Hari Kaskoyo (ULIN: Jurnal Hutan Tropis, 2021)
The existence of the LPHD is considered important, because it can improve the standard of living of the community around the forest area as well as be able to maintain the stability of the forest ecosystem, one of which is the LPHD Muara Danau, but its management is still considered not optimal in developing agroforestry businesses. This study aims to analyze the performance of the LPHD Muara Danau in village forest management. The research methodology are interviews, observation, and documentation studies. The data obtained were analyzed descriptively. Results showed that the performance of the Muara Danau LPHD was categorized as quite good, this was seen from three aspects, namely institutional, area and business management. The institutional management aspect is measured based on the participation of the management and LPHD members in participating in the activities as many as >75% of the members are present in the activity (91%) and the type of binding group rules in the form of (AD/ART) and unwritten rules (84%) and area management is measured based on types of forest resource conservation activities carried out were 52 people (95%) and the impact that was felt by 2-4 impacts on the environment from Village Forest management was 48 people (87%). However, business management has not yet achieved optimal results, measured based on the absence of local institutions (cooperatives) that carry out marketing of forest products. LPHD agroforestry business development needs to be increased in order to maximize the marketing of forest products.